Mental and Physical Symptoms and Perceived Health Risks of Pregnant and Postpartum Women following the Significant Shift in COVID-19 Management in China: A Cross-Sectional Survey. - Lai, Sha; Lu, Li; Wang, Yan-Ni; Yan, Yi-Zhu; Ma, Bing-Cun; Liu, Shou; Zhang, TianTian; Shen, Qing; Zhou, Zhongliang; Chen, Chang; Su, Yu-Qiang; Hu, Ying; et al. (Perspectives in Psychiatric Care, 2024)
Background. There was a remarkable downgrade in China's COVID-19 response strategies in January 2023. The COVID-19 infection rate grew rapidly in the early stages following the management policy shift. This study attempted to explore the associations between SARS-CoV-2 infection and mental or physical health status in pregnant and postpartum women and the role of perceived health risks and family members' SARS-CoV-2 infection status on these associations by capturing the impact of policy shifts in a short period of time. Methods. This cross-sectional study with a random sample from a convenience sample of hospitals was conducted in pregnant and postpartum women in January 2023. Standardized assessment tools were employed to assess anxiety, depressive and physical symptoms, and feelings of hopelessness. Hierarchical multiple logistic regressions were conducted to examine the mechanisms of associations of interests by including a range of sociodemographic factors, self-perceived health, SARS-CoV-2 infection status, and perceived health risks as covariates. Results. Of the 1,013 pregnant and postpartum women aged 32.0 ± 0.3 years, 58.2% (n = 590) were diagnosed with COVID-19, and 49.4% (n = 500) had family members who were infected with SARS-CoV-2. Nearly 98% of the included participants took measures to prevent SARS-CoV-2 infection. A COVID-19 diagnosis was positively associated with feelings of hopelessness (OR = 1.68, 95% CI: 1.20–2.35), probable anxiety (OR = 6.42, 95% CI: 2.18–24.61), possible depression (OR = 2.56, 95% CI: 1.07–6.70), and physical symptoms (OR = 6.28, 95% CI: 1.63–42.03) after adjusting for sociodemographic and health characteristics, while the associations presented no statistical significance when family members' SARS-CoV-2 infection status and perceived health risks were introduced into the models. Conclusions. Our results suggested that pregnant and postpartum women may experience physical and mental health challenges when they or their family members contracted COVID-19 in the context of a considerable shift in COVID-19 management. Early detection of poor health status and its risk factors for vulnerable groups during shifts in health policy and administrative practice is very necessary, and health services, including easy access to psychosocial support and obstetric counselling, should be prioritized.